R/V NATSUSHIMA NT14-03 Cruise Data - JAMSTEC (JAMSTEC, 2014)
[CRUISE DATA] This site includes a cruise dataset acquired in NT14-03 on R/V NATSUSHIMA from 2014-03-14 to 2014-03-21.
Observation contents: Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans